Investigation on fuel properties and engine performance of the extraction phase liquid of bio-oil/biodiesel blends. (March 2020) - Huang, Yongcheng; Li, Yaoting; Han, Xudong; Zhang, Jiating; Luo, Kun; Yang, Shangsheng; Wang, Jiyuan
Abstract: In this paper, biodiesel was used to upgrade bio-oil by extracting the high-quality fuel fractions in bio-oil through solvent extraction. After the extraction, the upper layer blends of biodiesel and the high-quality bio-oil components, also called the "extraction phase liquid", was obtained and denoted as EPBB. Firstly, Thermogravimetric (TG) and Fourier transform infrared (FTIR) analyses indicated that the light components originally in bio-oil, such as alcohols, ethers, ketones and carboxylic acids were extracted from bio-oil to biodiesel and formed the EPBB. Then the fuel properties of EPBB were measured at different temperatures. The results showed that the density of EPBB was higher, while its viscosity, surface tension and lower heating value (LHV) were lower than those of biodiesel. Accordingly, EPBB revealed better atomization and evaporation characteristics as compared to biodiesel. Finally, the engine performance of EPBB was tested on an unmodified direct-injection diesel engine. When compared with biodiesel, the ignition delay of EPBB was longer, the premixed combustion duration was longer, while the total combustion duration was shorter. The fuel economy of EPBB was comparable to that of biodiesel, and the NOx, soot, CO and UHC emissions of EPBB were all lower than those of biodiesel. Highlights: The renewable extraction phase liquid of bio-oil/biodiesel blends (EPBB) is prepared. EPBB is consisted of biodiesel and the best fuel fractions from bio-oil. The fuel atomization and evaporation of EPBB are better than those of biodiesel. EPBB has a comparable fuel economy and lower exhaust emissions than biodiesel.